Muscle fibre capillarization is a critical factor in muscle fibre hypertrophy during resistance exercise training in older men. Issue 2 (4th August 2016) - Snijders, Tim; Nederveen, Joshua P.; Joanisse, Sophie; Leenders, Marika; Verdijk, Lex B.; van Loon, Luc J.C.; Parise, Gianni
Abstract: Background: Adequate muscle fibre perfusion is critical for the maintenance of muscle mass; it is essential in the rapid delivery of oxygen, nutrients and growth factors to the muscle, stimulating muscle fibre growth. Muscle fibre capillarization is known to decrease substantially with advancing age. However, whether (relative) low muscle fibre capillarization negatively impacts the muscle hypertrophic response following resistance exercise training in older adults is unknown. Methods: Twenty‐two healthy older men (71 ± 1 years) performed 24 weeks of progressive resistance type exercise training. To assess the change in muscle fibre characteristics, percutaneous biopsies from the vastus lateralis muscle were taken before and following 12 and 24 weeks of the intervention programme. A comparison was made between participants who had a relatively low type II muscle fibre capillary‐to‐fibre perimeter exchange index (CFPE; LOW group) and high type II muscle fibre CFPE (HIGH group) at baseline. Type I and type II muscle fibre size, satellite cell, capillary content and distance between satellite cells to the nearest capillary were determined by immunohistochemistry. Results: Overall, type II muscle fibre size (from 5150 ± 234 to 6719 ± 446 µm 2, P < 0.05) and satellite cell content (from 0.058 ± 0.006 to 0.090 ± 0.010 satellite cells per muscle fibre, P < 0.05) had increased significantly in response to 24 weeks of resistance exercise training. However, these improvements where mainly driven by differences in baseline type II muscle fibre capillarization, whereas muscle fibre size (from 5170 ± 390 to 7133 ± 314 µm 2, P < 0.05) and satellite cell content (from 0.059 ± 0.009 to 0.102 ± 0.017 satellite cells per muscle fibre, P < 0.05) increased significantly in the HIGH group, no significant changes were observed in LOW group following exercise training. No significant changes in type I and type II muscle fibre capillarization were observed in response to 12 and 24 weeks of resistance exercise training in both the LOW and HIGH group. Conclusions: Type II muscle fibre capillarization at baseline may be a critical factor for allowing muscle fibre hypertrophy to occur during prolonged resistance exercise training in older men.